Biorefinery approach for the valorization of vine pruning residue - Jesus, Meirielly Santos (2016)
Lignocellulosic biomass (namely vine pruning residue, VPR) conversion into biofuels is considered a promising alternative to replace fossil fuels. In this work, VPR was submitted to hydrothermal treatment under isothermal conditions (180 and 200oC for 10-90min), in order to assess the effect of the treatment on the VPR fractionation. Liquid phase was analyzed for oligosaccharides composition and solid phase was submitted to enzymatic saccharification at liquid to solid ratio of 25 g/g and enzyme to substrate ratio of 25 FPU/g for glucose production. 62% of xylan was solubilized into xylose and xylooligosaccharides (2 and 11 g/L) and 70-98% of glucan remained in the pretreated VPR. Enzymatic saccharification of pretreated VPR was improved with the hardness of treatment. Overall, hydrothermal process (180oC, 60 min) was suitable for the production of xylose and xylooligosaccharides and to obtain a susceptible treated biomass for glucose production (13 g/L with 73% of conversion).